Ultrasonic-assisted extraction technique of fixed oils from Sudanese seeds - Taha Etigany, Hageramismaeel; Hayyan, Adeeb; Ahmed Ali, Emugdad; Abdalaziz, Mohamed Elmokhtar; Suliman, Mohamed; Elgharbawy, Amal A.M.; Mirghani, Mohamed Elwathig Saeed; Mohd Nor, Mohd Roslan; Mat Salleh, Muhammad Zulhaziman; Alkhandari, Khaled H.; Aldeehani, Ahmaad Kadmouse; Mohammed Al-Ramagha, Hamzah Fatehi; et al. (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2023)
The extraction of oils from Sudanese seeds is of great economic and traditional significance. This study investigated the use of ultrasonic-assisted extraction to extract oils from five different Sudanese seeds: desert date (Balanites aegyptiaca L), baobab (Adansonia digitata), peanut (Arachis hypogaea L.), watermelon (Citrullus lanatus), and roselle (Hibiscus sabdariffa). The extraction process used two organic solvents, n-hexane and n-heptane. The results showed that n-heptane was a more effective solvent for extracting oils from Sudanese seeds than n-hexane. The highest oil yield was obtained from B. aegyptiaca seeds, with a yield of 29%. The optimal seed-to-solvent mass ratio for B. aegyptiaca was 1:6, and the optimal extraction time was 1 hour (60 mins). A thermodynamic study was conducted to validate the experimental results. The larger area in the nonpolar region for n-heptane suggests a higher extraction capacity for the seed oils. These results are consistent with the experimental findings of this study. In conclusion, ultrasonic-assisted extraction is a promising method for extracting oils from Sudanese seeds. N-heptane is a more effective solvent than n-hexane for this purpose, and the optimal seed-to-solvent mass ratio and extraction time are 1:6 and 1 hour (60 mins), respectively. The results of this study could be used to develop new commercial products based on Sudanese seed oils. However, further research is needed to investigate the effects of other factors, such as temperature and pressure, on the extraction of oils from Sudanese seeds.